Efektivitas E-Modul Berbasis Inkuiri Terbimbing Dilengkapi Video Praktikum Pada Materi Kesetimbangan Kimia Terhadap Hasil Belajar Siswa - Elda Safarina; Andromeda Andromeda (Universitas Negeri Padang, 2022)
This research was conducted to continue previous research on the development of guided inquiry-based chemical equilibrium e-modules that have been tested for validity and practicality, but have not yet been tested for their effectiveness. The purpose of this study was to determine the level of effectiveness of the GIL-based chemical equilibrium e-module equipped with a practicum video that had been developed on the learning outcomes of class XI students of SMA N 1 Payung Sekaki. This research uses Pre-Experimental Design with One Group Pretest-Posttest design. The population includes students of class XI IPA 1 SMA N 1 Payung Sekaki in the academic year 2021/2022 and the sample is taken using a saturated sampling technique. Until l cover the entire population. This study uses a test instrument in the form of objective questions with validity, reliability, difficulty index, and discriminating power of questions that have good criteria. The level of effectiveness of the guided inquiry-based e-module equipped with a practicum video can be known after the N-Gain test is carried out. The N-Gain analysis on the sample class gave the results of the value of g = 0.58 in the medium category. This shows that the use of e-modules as a substitute for guided inquiry-based chemicals equipped with practical videos is effective in improving the learning outcomes of class XI students of SMA N 1 Payung Sekaki.